2014
DOI: 10.1111/jomf.12130
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Employment and Parenting Through Middle Childhood: Contextualizing Factors

Abstract: The authors used data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development (N = 1,364) to examine maternal work hour status and parenting (sensitivity and learning opportunities) from infancy through middle childhood. Work hour status was conceptualized as nonemployment, part time, and full time. Adjusting for covariates, mothers employed part time had higher sensitivity scores and higher provision of child learning opportunity scores than did mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 95 publications
0
31
0
Order By: Relevance
“…Research suggests that long work hours and high work–family conflict reduce this type of parent work (Ferreira et al, ; Viera et al, ). Yet others found that mothers' employment enhanced the quality of mothering for children from infancy to fifth grade and suggested that across social class levels, children benefited from mothers' multiple roles (e.g., worker, parent; Buehler, O'Brien, Swartout, & Zhou, ). These discrepant findings point to the need for greater specificity in how the relationship between parent work and paid work varies by children's developmental stage, work conditions, and family characteristics.…”
Section: Unpaid Work and Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that long work hours and high work–family conflict reduce this type of parent work (Ferreira et al, ; Viera et al, ). Yet others found that mothers' employment enhanced the quality of mothering for children from infancy to fifth grade and suggested that across social class levels, children benefited from mothers' multiple roles (e.g., worker, parent; Buehler, O'Brien, Swartout, & Zhou, ). These discrepant findings point to the need for greater specificity in how the relationship between parent work and paid work varies by children's developmental stage, work conditions, and family characteristics.…”
Section: Unpaid Work and Familiesmentioning
confidence: 99%
“…Blacks are more likely to work nonstandard hours (especially at night) and have more unpredictable work schedules than Whites (Boushey, ; Lambert, Fugiel, & Henly, ; McCrate, ; Su & Dunifon, ), but the measurement of race (e.g., White vs. other race; Black, Hispanic, other) often makes it impossible to specify differences across and within groups. Buehler et al () discussed how controlling for race and class masked important group differences. There are important exceptions.…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…The review indicates that a small number of studies utilized theoretical frameworks such as role expansion theory (Buehler, O'Brien, Swartout, & Zhou, 2014;Zhou & Buehler, 2016) and conservation-of-resources theory (Hobfoll, 1989) to guide hypothesis development or interpret results. Expansionist theory (Barnett & Hyde, 2001) posits that humans have abundant energy and that participation in one role can have a positive effect on other roles.…”
Section: Theoretical Limitations Of Past Studiesmentioning
confidence: 99%
“…Previous studies found that maternal employment and family socioeconomic status (SES) can differentially shape parenting and parental stress, which in turn shape children’s psychological adjustment (e.g., Buehler et al 2014; Chang 2013; Conger et al 2010; Cooklin et al 2015; Fuller et al 2002). However, existing research on maternal employment and family SES has predominantly sampled Western families.…”
Section: Introductionmentioning
confidence: 99%